Antibiotic residues in cattle and sheep meat and human exposure assessment in southern Xinjiang, China. Issue 11 (13th September 2021) - Zhang, Yu; Lu, Jianjiang; Yan, Yujun; Liu, Jinhua; Wang, Manli
Abstract: In recent years, antibiotics have become widely used in animal breeding. The application of antibiotics in livestock may lead to the presence of antibiotic residues in animal‐derived foods, especially meat, that may pose a threat to human health. In this study, 26 common antibiotics (eight sulfonamides, nine fluoroquinolones, four tetracyclines, and five macrolides) were screened in 88 meat samples (cattle muscles and sheep muscles, kidneys, and livers) obtained from southern Xinjiang. The antibiotics were screened via the clean‐up step based on solid‐phase extraction and determined through ultraperformance liquid chromatography–tandem mass spectrometry. Moreover, their risk to human health was analyzed. Overall, 16 antibiotics were detected with a total detection rate of 95.46%. The percentage of noncompliant samples was 28.41% with an exceedance maximum residue limit of 1.14%. The illegal use rate of the antibiotic norfloxacin was 27.27%. The estimated daily exposure doses of all compounds in adults were <102.218 ng/kg bw/day even after applying the worst‐case scenario approach. This result demonstrated that the antibiotic residues in the tested samples imposed negligible harm to people's health and had an acceptable level of food safety risk. However, the high detection frequencies found in this work indicated that the risk of antibiotic residues could not be ignored given the cumulative risk of antibiotics, particularly the emergence of bacterial resistance, to the human body. The need for effective strategies and publicity for the judicious use of antibiotics to safeguard residents' health is immediate. Abstract : Antibiotic residues in meat may lead to several adverse health effects, such as the development of multidrug‐resistant microbial strains, allergic and anaphylactic reactions, and the disruption of normal intestinal flora. In southern Xinjiang, cattle and sheep meats are popular among the local people because of the influence of the eating habits of ethnic minority residents. Therefore, the monitoring of antibiotic residues in meats from southern Xinjiang warrants particular attention. The results of this study could contribute to the understanding of relevant departments and researchers of the concentration and residue status of antibiotics in commercial cattle and sheep meats from southern Xinjiang. In addition, it could provide data support for source analysis and risk assessment, as well as a scientific basis for the control of antibiotic pollution sources. The results of this study also suggested that people need to reduce their dependence on antibiotics and look for alternatives to decrease drug risks.